E-learning SMANPAR: Sebuah Inovasi Pembelajaran Sejarah - Maulida, Elfa Rizkia (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
The development of information and communication technology has an impact on education, such as in the implementation of learning in schools. This is evidenced by the existence of E-learning SMANPAR as one of the outcomes of utilizing technology in education. E-learning SMANPAR offers features that support history learning. The conclusion of this research is that the presence of E-learning SMANPAR makes history learning more effective, provides diverse material presentation for students, and offers practical learning management for teachers. This is part of the innovation in history education through the utilization of technology to create engaging, relevant, and effective history learning for students, as well as presenting history materials in a more interactive format. For teachers, it makes learning management from planning, execution, to assessment more organized, efficient, and effective.